IMPLEMENTASI UPAH MINIMUM PROVINSI KALIMANTAN TIMUR TERHADAP USAHA KECIL DI KOTA SAMARINDA - Nur Shabrina Nadhilah (Universitas 17 Agustus 1945 Samarinda, 2020)
ABSTRACTThe application of wage methods in the field is not easy to implement. Although in Indonesia there has been an increase every year there are still some areas of workers/laborers who are not satisfied. For workers/laborers, the increase has not been able to help meet the needs of daily life. That there are some components that should be included in the components of the Decent Living Needs, but not included. In addition, the level of need that is increasing and expensive makes workers demanding an increase in the minimum wage.The type of research that I use is empirical juridical research, which is empirical juridical research, or called field research that examines the applicable legal provisions and what happens in reality in society.The results of the study stated that the implementation of the East Kalimantan Province Minimum Wage Against Small Businesses in Samarinda City has not been running well enough and maximally. This is because there are still companies in the form of PT or CV that have not paid the salaries of employees or laborers not in accordance with the applicable MSEs in the city of Samarinda for various reasons. can cover expenses and accompanied by workers who are not yet competent. Even though they have a competent workforce due to high operational costs, they are unable to pay their employees' salaries in accordance with the applicable MSEs in Samarinda. The obstacle of the implementation of the East Kalimantan provincial minimum wage to small businesses in Kota Samarinda is that the problem lies in the different contexts in each province and overlapping regulations. Whereas based on PP No. 78 of 2015, the increase in the minimum wage is determined by the current year's wage and national economic growth.Keywords: Wages, Business, City